Treatment with Helicobacter pylori-derived VacA attenuates allergic airway disease - Reuter, Sebastian; Raspe, Jonas; Uebner, Hendrik; Contoyannis, Alexandros; Pastille, Eva; Westendorf, Astrid M.; Caso, Georgia C.; Cover, Timothy L.; Müller, Anne; Taube, Christian (Frontiers in Immunology, 2023)
Background: Asthma is an incurable heterogeneous disease with variations in clinical and underlying immunological phenotype. New approaches could help to support existing therapy concepts. Neonatal infection of mice with Helicobacter pylori or administration of H. pylori-derived extracts or molecules after birth have been shown to prevent the development of allergic airway disease later in life. This study evaluated the potential therapeutic efficacy of H. pylori vacuolating cytotoxin A (VacA) in allergic airway inflammation asthma and investigated the underlying immunological mechanisms for its actions. Methods: Murine models of allergic airway diseases, and murine and human in vitro models were used. Results: In both an acute model and a therapeutic house dust mite model of allergic airway disease, treatment with H. pylori-derived VacA reduced several asthma hallmarks, including airway hyperresponsiveness, inflammation and goblet cell metaplasia. Flow cytometry and ELISA analyses revealed induction of tolerogenic dendritic cells (DC) and FoxP3 positive regulatory T cells (Tregs), and a shift in the composition of allergen-specific immunoglobulins. Depletion of Tregs during treatment with VacA reversed treatment-mediated suppression of allergic airway disease. Human monocyte derived DCs (moDC) that were exposed to VacA induced Tregs in co-cultured naïve autologous T cells, replicating key observations made in vivo. Conclusion: H. pylori-derived VacA suppressed allergic airway inflammation via induction of Tregs in both allergic airway disease models. These data suggest that the immunomodulatory activity of VacA could potentially be exploited for the prevention and treatment of allergic airway disease.